Correct folding of an α-helix and a β-hairpin using a polarized 2D torsional potential - Gao, Ya; Li, Yongxiu; Mou, Lirong; Lin, Bingbing; Zhang, John Z. H.; Mei, Ye (Scientific reports, 2015)
A new modification to the AMBER force field that incorporates the coupled two-dimensional main chain torsion energy has been evaluated for the balanced representation of secondary structures. In this modified AMBER force field (AMBER03 2D ), the main chain torsion energy is represented by 2-dimensional Fourier expansions with parameters fitted to the potential energy surface generated by high-level quantum mechanical calculations of small peptides in solution. Molecular dynamics simulations are performed to study the folding of two model peptides adopting either α-helix or β-hairpin structures. Both peptides are successfully folded into their native structures using an AMBER03 2D force field with the implementation of a polarization scheme (AMBER03 2D p). For comparison, simulations using a standard AMBER03 force field with and without polarization, as well as AMBER03 2D without polarization, fail to fold both peptides successfully. The correction to secondary structure propensity in the AMBER03 force field and the polarization effect are critical to folding Trpzip2; without these factors, a helical structure is obtained. This study strongly suggests that this new force field is capable of providing a more balanced preference for helical and extended conformations. The electrostatic polarization effect is shown to be indispensable to the growth of secondary structures.